”An Appraisal studies on moral deviation and It’s therapy through Manfalouti’s book “Al- Nazaraat - Inusa, Wedraoga; Ben Abdel Halim, Tho Al Azhan (Journal of Humanities & Social Sciences, 2019)
Manfalouti’s literary works are recognized in addressing social issues. This is because the stories and articles are critical in the descriptions of reality. Most of these descriptions are found in his book ‘Al- nazarat”, where the author enlightens and motivates the public toward the independence of minds and respect as well as love with dignity and talent. The author focuses on the criticism of writers, journalists, poets, linguists, and the aspects of politics, social corruption resulting from the influence of western civilization, and resolution of marital and educational issues, as well as evaluation of moral deviations and call for good morals. This study highlights the evaluation of moral deviations and call for good morals using descriptive and analytical methods, by relating the similarities of the issues covered in the book, drawing conclusion based on the thoughts advocated by the author under each issue. The study discovered eight moral deviations which the author avoids and disregards those who practice them in different ways: theft, laziness, envy, arrogance, miserliness, dishonesty, alcohol, gambling. In addition, the author calls for five good morals: righteousness, integrity, patience, loyalty, and compassion.